Laparo‐endoscopic rendezvous using a single balloon endoscope for cholecysto‐choledocholithiasis in a patient with roux‐en Y. Issue 5 (12th July 2019) - Iwaya, Hiromichi; Hashimoto, Shinichi; Ido, Akio
Abstract : Watch a video of this article